Improving patient satisfaction through improved telephone triage in a primary care practice. Issue 4 (2nd December 2019) - Vitale, Rebecca; Smith, Samantha; Doolittle, Benjamin R
Abstract : Objective: The objective of this study was to improve the telephone communication experience for patients in a primary care practice. Design: An exploratory survey was conducted that revealed suboptimal patient satisfaction with clinic access due to the telephone triage system. Several interventions were designed: a monthly quality meeting was established among clinic staff, all phone interactions were recorded in the electronic medical record (EMR) and clinic appointments were made available several months in advance. A follow-up survey was conducted to evaluate these interventions. Setting: The study was conducted in a multispecialty, urban-based, resident-faculty practice from November 2016 to November 2017. Participants: Subjects were recruited in a convenience sample from the waiting room. 200 subjects participated in the initial survey and 215 in the second survey. Results: After the interventions, patients felt that their questions were answered more frequently than before (p<0.01). They also felt that appointments were easier to make (p=0.03). A similar number of patients reported seeking emergency care because they were unable to reach a provider (33.8% vs 31.9%, p=0.68). The percentage of patients who received a call back within 24 hours increased, but it was not statistically significant (38.6% vs 44%, p=0.13). Conclusion: Improving telephone triage through implementing a monthly quality improvement meeting, optimising use of the EMR and opening schedules several months in advance resulted in several improvements in the patient experience, but did not change use of emergency services. Further interventions, including increased resource allocation, are needed to optimise patient experience.